CIAT Germplasm Bank Database - International Center for Tropical Agriculture (2014)
Search CIAT’s collection of over 36,000 bean varieties, 6,500 cassava materials and 23,000 tropical forages materials. For those looking for a particular plant material in the collection, instructions for making a germplasm request are available.